Web based learning on KBSM chemical formulae incorporating selected multiple intelligences - Ali, Mohamad Bilal; Nair G., Divya (2010)
Vision 2020 aspires our nation to establish a progressive and resourceful society that is able to contribute to the scientific and technological civilisation of the future. One of the strategies to achieve this aspiration would be through the system of education whereby web based learning would be a good platform to begin with. The aim of this project is to develop a website for KBSM Chemistry Form Four for the subtopic Chemical Formulae, which is under the topic Chemical Formulae and Equations, Chapter 3. The aim of this website is to provide a web based learning platform for students to learn Chemical Formulae. The theory of Multiple Intelligences has been incorporated in the development of this website. However, only four multiple intelligences are selected in delivering the learning contents. The four intelligences selected are Verbal Linguistics, Logical Mathematical, Visual Spatial and Interpersonal. The Hannafin & Peck Model was adapted throughout the development process, which includes Needs Assessment, Design and Development/ Implementation Phase. Evaluation was carried out simultaneously during all three phases of development. The primary software used in developing this website is Microsoft Office Frontpage. Integration of multimedia elements such as graphics, video and animation are used to enhance the process of learning. It is hoped that this website would benefit students with the selected four intelligences at an optimum level in learning Chemical Formulae.